Characterization of commercial detergents and natural cleansing agents with comparison of their potential for biodegradability - Mer, Anjali; Samant, Rajesh; Padmanabha, Prabha (International Journal of Advanced Chemistry, 2017)
Background: Commercial detergents are chemical formulations designed to dissolve or disperse grease, grime, and dirt by making them water soluble or suspending it in water. They are best known for their wide use in laundry industry and household cleaning. After use, the wash waters along with the residual detergents are discharged into sewage system and are carried to water bodies, which result in damaging the biodiversity of aquatic environment due to the non-degradable nature of the active detergent matter present in these cleansing agents.Method: A critical analytical study was conducted on the quality of popular detergent powders sold in the Indian market viz. Ariel, Surf Excel, Rin and Tide with respect to their moisture content, active and total alkalinity, active detergent matter, water-insoluble matter, oxygen releasing capacity and pH. Two natural cleansing agents viz. Areetha and Shikakai were tested for the same parameters. Bacterial cultures were isolated from detergent-rich soil in Dhobighat, Mumbai and used to study detergent degradation over a period of time. Methylene Blue Photometric Assay was used to estimate the reduction in active detergent matter.Result and Conclusion: Areetha and Shikakai were found effective as detergents but with certain limitations. Degradation was seen in the commercial detergents over a period of time.